An intergrated approach in records management at Sable Chemical industry (2008-2016). - Mavhangira, Moreblessing (Midlands State University, 2017)
The study presents an integrated approach in records management for Sable chemical Industry during the period of 2008 to 2016.An integrated approach is a system used in records management in which the combination of paper based records and electronic records work hand in hand in records keeping. The study however established that there is seemingly misplacement as and missing of files in the presents of an integrated approach of electronic and paper records. The study therefore intends to evaluate the effectiveness of the implemented hybrid system within the organization. In order for the study to address the main aim, it looks on how the hybrid system has been implemented at the organization. The research also ascertains the standard and procedures that have been used by the organization. It also makes analysis of staff competence in the implemented hybrid system. The study also makes an identification of challenges that the organization is facing in the implementation of the system. The study is justifiable as it stands as a guide and key informant to future researches. Using interviews and observations, data was collected from three departments of the organization which are the Records Section, the Human resource Department as well as the Information Technology department. A total number of 9 respondents was used which include departmental supervisors, IT experts and records Officers. The main findings of the study were also been presented in the study. The study recommends the staff to be trained in records management practices, to have policies, standards and procedures which guide management of both paper and electronic records. The study also recommends the organization to seek funds from well-wishers and donors to improve management system of records.